New species of Coelinius Nees (Hymenoptera: Braconidae: Alysiinae) from Brazil - de Oliveira, Franciélle Dias; Penteado-Dias, Angélica Maria (Zootaxa, 2022)
A new species of Alysiinae wasp, Coelinius longicephalus sp. nov., from Brazil is described. Additional information is also provided for other species of the genus known in Brazil, namely, C. canastra Souza-Gessner & Penteado-Dias, C. itamonte Souza-Gessner & Penteado-Dias, C. kali Souza-Gessner & Penteado-Dias, and C. lux Souza-Gessner & Penteado-Dias. A dichotomous identification key to the neotropical species of Coelinius is provided.